Characterization of novel human papillomavirus types 157, 158 and 205 from healthy skin and recombination analysis in genus γ-Papillomavirus - Bolatti, Elisa Maria (2016)
Gammapapillomavirus (γ-PV) is a diverse and rapidly expanding genus, currently consisting of 79 fully characterized human PV (HPV) types. In this study, three novel types, HPV157, HPV158 and HPV205, obtained from healthy sun-exposed skin of two immunocompetent individuals, were amplified by the "Hanging droplet" long PCR technique, cloned, sequenced and characterized. HPV157, HPV158 and HPV205 genomes comprise 7154-bp, 7192-bp and 7298-bp, respectively, and contain four early (E1, E2, E6 and E7) and two late genes (L1 and L2). Phylogenetic analysis of the L1 ORF placed all novel types within the γ-PV genus: HPV157 was classified as a new member of species γ-12 while HPV158 and HPV205 belong to species γ-1. We then explored potential recombination events in genus γ-PV with the RDP4 program in a dataset of 74 viruses (71 HPV types with available full-length genomes and the 3 novel types). Two events, both located in the E1 ORF, met the inclusion criterion (p-values <. 0.05 with at least four methods) and persisted in different ORF combinations: an inter-species recombination in species γ-8 (major and minor parents: species γ-24 and γ-11, respectively), and an intra-species recombination in species γ-7 (recombinant strain: HPV170; major and minor parents: HPV-109 and HPV-149, respectively). These findings were confirmed by phylogenetic tree incongruence analysis. An additional incongruence was found in members of species γ-9 but it was not detected by the RDP4. This report expands our knowledge of the family Papillomaviridae and provides for the first time in silico evidence of recombination in genus γ-PV.